Pengaruh Work overload dan Work stress Terhadap Employee performance pada Organisasi Sektor Publik Sub Sektor Kesehatan - Nindya Joandis Puteri; Vika Aprianti; Aggi Panigoro Sarifiyono (Economics Professional in Action (E-Profit), 2024)
This research aims to determine the state of work overload, work stress, and employee performance and to find out the magnitude of the influence of work overload, work stress, on employee performance in Public Sector Organizations, Health Sub-Sector, UPT Padasuka Community Health Center, Bandung City, both partially and simultaneously. The method used in this research is a descriptive and verification method with a quantitative approach. The population used in this research were all employees of the UPT Padasuka Health Center, Bandung City, totaling 62 people using a non-probability sampling technique, namely purposive sampling by determining the sample based on the criteria for employees as medical personnel, amounting to 40 samples. Based on the research results, it was found that work overload and work stress were in the high category and employee performance was in the low category. Based on the results of the determination test, work overload has a 42.3% effect on employee performance, work stress has a 32.0% effect on employee performance, work overload and work stress have a 50.3% effect on employee performance. The partial research results have a tcount value of -4.043 > ttable -2.026 and a sig. 0.000 < 0.05 shows that work overload has a negative and significant effect on employee performance, the tcount value is -2.870 > ttable -2.026 and the sig value. 0.007 < 0.05 indicates work stress has a negative and significant effect on employee performance. Simultaneously the Fcount value is 20.702 > Ftable 3.25 and the sig value. 0.000 < 0.05 indicates work overload and work stress have a significant effect on employee performance.